The Influence Of Supplier Relationship Management On The Performance Of Manufacturing Companies In Makassar City - Darmawangsyah, Darmawangsyah; Mahfudnurnajamuddin, Mahfudnurnajamuddin; Serlin Serang (Jurnal Ekonomi, 2024)
This study aims to examine the impact of Supplier Relationship Management (SRM) on the performance of manufacturing firms in Makassar. The research employed a descriptive design, collecting data from a sample of manufacturing firms through structured questionnaires. The analysis used regression techniques to explore the relationship between SRM practices, such as early supplier involvement, supplier development, and joint investment, and organizational performance. Findings revealed a significant positive correlation, indicating that enhanced SRM practices contribute to improved efficiency, reduced costs, and better alignment within the supply chain. The study also highlights the importance of government support in facilitating effective SRM strategies for sustainable industrial growth.